Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1-\frac{sin^3x}{sinx+cosx}-\frac{cos^3x}{sinx+cosx}=1-\frac{sin^3x+cos^3x}{sinx+cosx}\)
\(=1-\frac{\left(sinx+cosx\right)\left(sin^2x+cos^2x-sinx.cosx\right)}{sinx+cosx}=1-\left(1-sinxcosx\right)\)
\(=sinx.cosx\)
\(A=sinx.cosx+\frac{1-cos^2x}{1+\frac{cosx}{sinx}}+\frac{1-sin^2x}{1+\frac{sinx}{cosx}}\)
\(=sinx.cosx+\frac{\left(sinx-sinx.cosx\right)\left(1+cosx\right)}{1+cosx}+\frac{\left(cosx-sinx.cosx\right)\left(1+sinx\right)}{1+sinx}\)
\(=sinx.cosx+sinx-sinx.cosx+cosx-sinx.cosx\)
\(=sinx+cosx-sinx.cosx\)
\(cosx=\sqrt{1-\dfrac{7}{16}}=\dfrac{3}{4}\)
\(tanx=\dfrac{\sqrt{7}}{4}:\dfrac{3}{4}=\dfrac{\sqrt{7}}{3}\)
\(cotx=1:\dfrac{\sqrt{7}}{3}=\dfrac{3}{\sqrt{7}}=\dfrac{3\sqrt{7}}{7}\)
\(M=\left(\dfrac{3}{7}\sqrt{7}+\dfrac{1}{3}\sqrt{7}\right):\left(\dfrac{3}{7}\sqrt{7}-\dfrac{1}{3}\sqrt{7}\right)\)
\(=\dfrac{16}{21}:\dfrac{2}{21}=8\)